Calcium, Iron, and Zinc Bioaccessibilities of Australian Sweet Lupin (Lupinus angustifolius L.) Cultivars - Karnpanit, W.; Coorey, Ranil; Clements, J.; Benjapong, W.; Jayasena, Vijay (American Chemical Society, 2017)
© 2017 American Chemical Society. In this study, we aimed to determine the effect of the cultivar and dehulling on calcium, iron, and zinc bioaccessibilities of Australian sweet lupin (ASL). Ten ASL cultivars grown in 2011, 2012, and 2013 in Western Australia were used for the study. The bioaccessibilities of calcium, iron, and zinc in whole seed and dehulled lupin samples were determined using a dialysability method. The cultivar had significant effects on calcium, iron, and zinc contents and their bioaccessibilities. Average bioaccessibilities of 6% for calcium, 17% for iron, and 9% for zinc were found for whole seeds. Dehulled ASL had average calcium, iron, and zinc bioaccessibilities of 11%, 21%, and 12%, respectively. Compared to some other pulses, ASL had better iron bioaccessibility and poorer calcium and zinc bioaccessibilities. Dehulling increased calcium bioaccessibilities of almost all lupin cultivars. The effect of dehulling on iron and zinc bioaccessibilities depends on the ASL cultivar.